Beyond bricolage: social innovation as systematic, consistent and repeatable process - Curtis, Timothy (NOvation — Critical Studies of Innovation, 2023)
This paper provides empirical research demonstrating that there are clear, consistent and repeatable processes at play in social innovation, calling into question the currently hegemonic postmodernist concept of ‘social bricolage’ in social innovation literature. The paper applies a critical realist & systems analysis approach, utilising Checkland’s (1981/2000) Soft Systems Methodology (SSM). The research project investigated 8 neighbourhood and community policing projects using a handbook called Locally identified Solutions & Practices (LISP). LISP was implemented in a range of different social contexts to construct context-mechanism-outcome (CMO) chains (after Pawson, 2013) in a two-step process to identify which social innovation mechanisms contributed to what outcomes in which contexts. The paper reports on empirically based evidence of social innovation processes that do not rely on the characteristics of the individual social entrepreneur or the serendipity of social bricolage ‘freeplay’ (Derrida, 1970). The paper makes the case that social innovation is more than ‘bricolage’ (Derrida, 1970; Di Domenico et al., 2010), not an eclectic mysterious craft of innovation that relies on the skills and characteristics of the social entrepreneur, but instead a systematic, consistent and repeatable process.